2021
DOI: 10.1007/s11244-021-01435-y
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Experimental Procedures for the Application of Infrared Spectroscopy to Probe the Surface Morphology of an Alumina-Supported Palladium Catalyst

Abstract: Structure/function relationships in heterogeneous catalysis play an important role in catalyst design strategies. The combination of chemisorption of suitable probe molecules alongside application of infrared spectroscopy is an established technique for providing information on the metal crystallite morphology of supported metal catalysts. Following a review of key literature on this topic, a variety of experimental arrangements that may be adopted for this task are examined. Specifically, the adsorption of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Bridge-bonded CO was held more strongly on the catalyst and was still present in the spectrum collected after the maximum desorption temperature of 450 °C. These results agree with previous CO TP-IR measurements for 5 wt % Pd/Al 2 O 3 catalysts, 29 , 40 indicating GU-1 to provide a useful reference material on which to consider morphological effects on hydrogenation activity.…”
Section: Results and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Bridge-bonded CO was held more strongly on the catalyst and was still present in the spectrum collected after the maximum desorption temperature of 450 °C. These results agree with previous CO TP-IR measurements for 5 wt % Pd/Al 2 O 3 catalysts, 29 , 40 indicating GU-1 to provide a useful reference material on which to consider morphological effects on hydrogenation activity.…”
Section: Results and Discussionsupporting
confidence: 91%
“… 40 The significance of distinguishing between CO adsorption on corner and edge sites, adsorption sites proposed to be involved in hydrogen supply, 40 42 via DRIFTS has previously been considered. 29 Furthermore, and central to this study, is to note that the profile of the ambient temperature infrared spectrum shown in Figure 2 is indicative of the Pd crystallites adopting a truncated cuboctahedron structure. 40 Thus, catalytic turnover on GU-1 can be considered as occurring on the Pd surface sites, as revealed within Figure 2 .…”
Section: Results and Discussionmentioning
confidence: 92%
See 3 more Smart Citations